Adenosine diphosphate stimulates VEGF-independent choroidal endothelial cell proliferation: A potential escape from anti-VEGF therapy - Nilima Biswas; Tommaso Mori; Naresh Kumar Ragava Chetty Nagaraj; Hong Xin; Tanja Diemer; Pin Li; Yongxuan Su; Carlo Piermarocchi; Napoleone Ferrara (Proceedings of the National Academy of Sciences, 2025)
We hypothesized that a strategy employing tissue-specific endothelial cells (EC) might facilitate the identification of tissue- or organ-specific vascular functions of ubiquitous metabolites. An unbiased approach was employed to identify water-soluble small molecules with mitogenic activity on choroidal EC. We identified adenosine diphosphate (ADP) as a candidate, following biochemical purification from mouse EL4 lymphoma extracts. ADP stimulated the growth of bovine choroidal EC (BCEC) and other bovine or human eye-derived EC. ADP induced rapid phosphorylation of extracellular signal-regulated kinase in a dose- and time-dependent manner. ADP-induced BCEC proliferation could be blocked by pretreatment with specific antagonists of the purinergic receptor P2Y1 but not with a vascular endothelial growth factor (VEGF) inhibitor, indicating that the EC mitogenic effects of ADP are not mediated by stimulation of the VEGF pathway. Intravitreal administration of ADP expanded the neovascular area in a mouse model of choroidal neovascularization. Single-cell transcriptomics from human choroidal datasets show the expression of P2RY1, but not other ADP receptors, in EC with a pattern similar to VEGFR2. Although ADP has been reported to be a growth inhibitor for vascular EC, here we describe its growth-stimulating effects for BCEC and other eye-derived EC.